Nontuberculous mycobacterial infection as a cause of difficult-to-control asthma: a case-control study - Fritscher, Leandro G; Marras, Theodore K; Bradi, Ana C; Fritscher, Carlos C; Balter, Meyer S; Chapman, Kenneth R (Chest, 2011)
Symptomatic disease due to nontuberculous mycobacteria (NTM) is known to occur commonly in the presence of structural lung disease, but is not described in association with asthma. This was a case-control study nested in a cohort. We identified 22 patients with difficult asthma referred to a tertiary academic referral center and subsequently found to have infection with NTM. We matched each case with two control subjects (next two consecutive patients referred for asthma management). It took on average 2.1 years from the onset of new or worsening symptoms to NTM diagnosis. The most common symptoms were worsening cough (77%), sputum production (40.9%), and frequent exacerbations (31.8%). Mycobacterium avium complex accounted for 63.6% of the infections, Mycobacterium xenopi the balance. Case subjects were older (59.8 ± 8.9 vs 42.6 ± 18 years; P < .001) and had more severe airflow obstruction (FEV(1), 57% [40%-74%] vs 89.5% [80%-98%]; P < .001). There was no difference between case and control subjects in the proportion using inhaled corticosteroids (ICS) or the average daily dose at the time of presentation, but case subjects had used ICS for a longer period (17 [6.2-20] vs 4 [0.75-6.0] years; P=.002). Six subjects with NTM were being treated with daily oral steroids, whereas none of the control subjects was. Of the 22 cases, 10 were treated with antibiotics for NTM, seven demonstrating clinical improvement or resolution of the presenting symptoms. NTM infection can be associated with asthma and should be considered in difficult-to-treat disease, especially in older individuals with more severe airflow obstruction and greater exposure to inhaled or systemic corticosteroids.